PENGARUH DOSIS PUPUK P DAN PUPUK KANDANG KERBAU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG HIBRIDA (Zea mays. L) - Sumarto Sumarto; Teguh Supriyadi Teguh Supriyadi; Agus Budiono Agus Budiono (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2010)
The research aim to know influence of dosage fertilizer Phosphor SP36) and buffalo manure to growth and result plant hybrid corn. Research was conducted since February until Juny 2008 in Kedokan Sayang Village, Sub District Tarub, District Tegal, Central Java, Altitude 25 meters from sea surface with soil type alluvials, in the Laboratory of Agriculture Faculty, Tunas Pembangunan University. Temperature 29 â€“ 32 Âº C. Research used the factorial with based pattern RCBD (Randomized Completely Block Design) consist of 2 treatment factor with 3 times restating. Results of research indicates that : (1) Fertilization dosage with fertilizer SP36 influentially very significant to weight total fresh plant, weight total dry plant, number of seeds per cob, weight dry minner per plant, weight dry minner per plot and weight dry minner per 100 seeds. (2) Fertilization dosage with buffalo manure influentially significant to hight of plant and hight of 100 seeds (3) Interaction between fertilization dosage with fertilizer SP36 and buffalo manure influentially significant to hight of 100 seeds. (4) Highest dry minner seeds weight 5,467 Kg/plot (9,719 ton/Ha) obtained at treatment of P2K2 combination of fertilizer dosage SP36 150 Kg/Ha with buffalo manure 15 ton/Ha, and lowered by 3,833 Kg/plot (6.6614 ton/Ha) obtained at treatment of P0K2 combination of fertilizer dosage SP36 0 Kg/Ha with buffalo manure 15 ton/Ha